MORAL AND ETHICAL ASPECTS OF HUMAN-TECHNOLOGY INTERACTION IN THE CONTEMPORARY INFORMATION SOCIETY: A SOCIO-PHILOSOPHICAL CONTEXT - Sidorkina , Olena (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
The contemporary information society is characterized by profound transformations that encompass all spheres of human life. Technology and technical means are becoming not only instruments but also an environment that shapes new social practices. In this context, moral consciousness emerges as a key factor capable of ensuring a balance between innovation and humanistic values. The aim and tasks. The aim of the article is to analyze the contemporary type of moral consciousness and to define the role of the moral and ethical component as a factor guiding technological development in the interests of society from the standpoint of a socio philosophical approach. Research methods. The theoretical and methodological foundation of the article is based on the main theoretical principles of the dialectical approach, the principles of the systemic approach, as well as the provisions and issues of the ethics of science and technology. Research results. In the modern world, moral consciousness emerges not as a static system of norms but as a dynamic structure that continuously expands and adapts to new challenges. From a socio-philosophical perspective, it is understood as a multidimensional system that integrates individual values (dignity, responsibility, compassion), collective norms (justice, equality, trust), and global standards (sustainable development, harmony, peace). Discussion. A socio- philosophical analysis of the moral and ethical aspects of human–technology interaction is grounded in several key principles. First, technology is understood as a second nature” of humanity, an extension that reflects social values, goals, and limitations rather than remaining neutral. Second, moral consciousness functions as a social regulator, setting boundaries for the acceptable use of technology. Third, the rise of the information society introduces a qualitatively new context, where digitalization, artificial intelligence, and global communication networks generate new ethical dilemmas and challenges. Conclusion. The contemporary type of moral consciousness is formed as a multidimensional system that integrates knowledge, experience, creativity, and humanistic values. The ethical frameworks of technological progress ensure its orientation not only toward efficiency but also toward justice, dignity, and the integrity of human existence, allowing it to be considered within the context of a unified history of development, where the past, present, and future constitute a continuous chain of succession.